Biocomposite foams consisting of microencapsulated phase change materials for enhanced climatic regulation with reduced carbon dioxide emissions in buildings - Gencel, Osman; Aydogmus, Ercan; Guler, Onur; Ustaoglu, Abid; Sari, Ahmet; Hekimoglu, Gokhan; Marasli, Muhammed (Elsevier Sci Ltd, 2024)
Using polyurethane foam (PUF) matrix-based phase change material-enhanced composites is crucial for improving energy efficiency, enhancing thermal regulation, and reducing environmental impact in buildings. Integrating bio-components into PUF production and using these bio-composite foams (BPUFs) as the matrix offers environmentally friendly and structurally advanced solutions. Microencapsulated phase change material (MPCM) further enhances these foams, creating innovative, high-performance, eco-friendly composites for building applications. In this context, the biocomponent castor oil (CO) to be used in BPUF production has been modified with epoxy. BPUF-MPCM biocomposites with different compositions were produced using MPCM in the range of 0-90 wt% and modified castor oil (MCO) in the range of 0.75-7.50 wt% in BPUF production. The addition of 90 wt% MPCM content in BPUF-MPCM biocomposites has facilitated the attainment of a melting enthalpy value of 176.8 J/g (at 25.4 C-degrees) while providing a solidification enthalpy value of 175.7 J/g (at 20.8 C-degrees). The advancements in the microstructure of BPUF-MPCM composites contribute to physical improvements, such as a more homogeneous cell structure and enhancements in thermal transformation properties, thereby contributing to their thermoregulatory characteristics. BPUF-MPCM 90 wt% composites have achieved 100 % energy savings and zero CO2 emission values by varying material thicknesses across all climate conditions.
Keywords: Biocomposite; Polyurethane foam; Microencapsulated phase change material; renewable energy; Energy and energy efficiency; Carbon emission reduction